Effects of Herbal Medicines on the Prevention and Treatment of Contact Dermatitis: A Systematic Review - Sedigheh Rastegar; Ghazaleh Heydarirad; Zeinab Aryanian; Maryam Shekofteh; Azam Shahbodaghi; Shirin Fahimi; Azadeh Goodarzi; Sanaz Poshtmahi (Tehran University of Medical Sciences, 2022)
Background: Contact dermatitis (CD) is a common inflammatory disease of the skin. CD has a complex and multifaceted treatment, and one of the main components of CD treatment is inflammation management. We summarized the clinical trials exploring the effects of herbal medicine on patients with CD. Methods: A systematic review was performed by searching four databases. Clinical trials in English investigating the effect of herbal medicines on CD prevention and treatment published from 2010 to 2020 were reviewed. This study was conducted based on the PRISMA guidelines. Results: Nine clinical trials examining the effects of herbs on CD were identified. A total of 450 patients participated in these studies. Herbal medicines used in the reviewed studies were in various forms. Almost all the studies showed that these herbs were useful in preventing and treating CD. Regarding the side effects of the herbal medicines, few complications such as erythema and papules as well as positive chronotropic effects were reported. Conclusion: Evidence showed that herbal medicines were effective in preventing and treating CD by reducing the inflammation level and increasing antioxidant defense. However, the number of clinical trials was low to draw definitive conclusions. Moreover, the studies were not homogeneous and differed regarding methodology, evaluation tools, and quality. Also, in these studies, the interactions and safety of the herbal medicines were not considered adequately. Therefore, well-designed evidence is required to draw definitive conclusions in this regard.